Nicotine treatment ameliorates DSS‐induced colitis by suppressing MAdCAM‐1 expression and leukocyte recruitment. Issue 5 (14th June 2018) - Maruta, Koji; Watanabe, Chikako; Hozumi, Hideaki; Kurihara, Chie; Furuhashi, Hirotaka; Takajo, Takeshi; Okada, Yoshikiyo; Shirakabe, Kazuhiko; Higashiyama, Masaaki; Komoto, Shunsuke; Tomita, Kengo; Nagao, Shigeaki; et al.
Abstract: The enhanced recruitment of leukocytes to the inflamed colon is a key feature of ulcerative colitis (UC). The gut‐specific adhesion molecules involved in leukocyte recruitment have emerged as recent therapeutic targets. Nicotine absorbed from smoking has been reported to work protectively in UC patients. Our hypothesis is that nicotine may suppress the aberrant leukocyte recruitment and colonic inflammation via the suppression of the overexpressed gut‐specific adhesion molecules in the inflamed colon. To test this hypothesis, the severity of colitis and the degree of leukocyte recruitment induced by gut‐specific adhesion molecules were assessed in dextran sulfate sodium (DSS) colitis mice (C57BL/6J mice treated with 3% DSS) with or without nicotine treatment. We also studied the in vitro changes in the expression of adhesion molecules by using a vascular endothelial cell line. DSS‐induced colitis was accompanied by increases in disease activity index (DAI), histological score, recruitment of leukocytes, and the expression of adhesion molecules, mucosal vascular addressin cell adhesion molecule‐1 (MAdCAM‐1) and VCAM‐1. Nicotine treatment significantly attenuated MAdCAM‐1 expression, leukocyte recruitment, DAI, and histological score. The expression of β7‐integrin, the ligand for MAdCAM‐1, on leukocytes was not affected by nicotine treatment. In vitro study, the TNF‐α‐enhanced mRNA expression of MAdCAM‐1 was reduced by the coadministration of nicotine in a dose‐dependent manner, possibly via nicotinic receptor activation. These results supported our hypothesis that nicotine treatment ameliorated colitis through the suppression of MAdCAM‐1 expression on the microvessels in the inflamed colon. Further investigation is warranted on the role of nicotine in the treatment of UC. Abstract : Nicotine ameliorated the over‐expressed MAdCAM‐1 and inhibited leukocyte recruitment in murine colitis.